Status karies mahasiswa non kedokteran gigi pengguna alat ortodontik cekat di Universitas Udayana - Nyoman Surya Permata Sari; Putu Ika Anggaraeni; Sari Kusumadewi (Bali Dental Journal, 2018)
Background: The use of fixed orthodontic appliance without knowledge and appropriate action during treatment will cause problems in the mouth and teeth. Parts of fixed orthodontic appliances can cause food debris attach to the teeth and make cleaning or brushing the teeth difficult. Thus potentially create a new environment for bacteria and cause caries. Aim: The aim of this study is to know the caries status of non dentistry student using fixed orthodontics appliance at Udayana University. Method: This is a descriptive study with cross sectional design. Sample was determined using purpose sampling technique accordance to the inclusion criteria. Data was obtained by using an index of Decay Missing Filling Teeth (DMF-T). Results: The results of the study showed 57 respondents were exposed to caries (77%) and 17 respondents were free of caries (23%). Status of caries showed the number of DMF-T in average 3,6 and is included as intermediate level (based on the category of index of DMF-T WHO). Conclusion: It can be concluded that the caries status of non dentistry student using fixed orthodontic appliance at Udayana University was in intermediate level.